The Role of Banquet Waiters in Handling Meeting Events at the Saka Hotel Medan - Arifin, Muhammad Nur (Cattleya Darmaya Fortuna, 2024)
Banquet is a department in the hotel and is responsible for handling various kinds of events that have been ordered by guests, such as meetings. In handling meeting events at hotels, Banquet waiters play a very important role including the duties and responsibilities of handling the event, preparing the necessary things and arranging the layout of the meeting room before the meeting event takes place. To obtain data, the author made direct observations in the field, namely Hotel Saka Medan, using data collection techniques in the form of library research and field research through direct interviews with the Food & Beverage Service. In this case, the population in the research is 1 banquet manager and 5 banquet waiter's staff. The author's aim in conducting research is to find out the progress and development of existing science and technology, especially in the hotel sector. The results of this article can be input for hotel management, especially in the banquet sector, in terms of the duties and responsibilities of banquet waiters, event meeting preparations, efforts to overcome obstacles. during meeting event activities. There are several conclusions that the author has reached, namely, the level of awareness of banquet waiter responsibilities is still lacking, and in preparation there are still several shortcomings, especially in utilizing training students at each event. From this conclusion, the author suggests that banquet managers should pay more attention to the duties and responsibilities of banquet waiters as well as make better preparations so that the implementation of event meeting activities can run well and smoothly.